The prevalence of obesity and influence of early life and behavioral factors on obesity in Chinese children in Guangzhou - Ting Zhang; Li Cai; Lu Ma; Jin Jing; Yajun Chen; Jun Ma (BMC, 2016)
Abstract Background Childhood obesity has become a public health concern in many countries. In Southern China, the prevalence of childhood obesity increased from 6.2 to 7.5 % between 2007 and 2011. This study aimed to report the current prevalence of overweight and obesity, analyzed the early life and behavioral determinants of obesity, and investigated the weight-loss practices among Chinese children in Guangzhou. Methods Three thousand seven hundred sixty-six primary school students aged 7-12 years were recruited in Guangzhou, China in 2013. Questionnaires were used to assess (1) early life factors: birth weight, delivery mode, gestational age and feeding patterns; (2) behavioral factors: dietary intake, eating speed, sedentary time, physical activities and sleep duration; and (3) weight-loss practices: improving diet, increasing exercise, taking weight-loss drugs and undergoing a diet. The criteria of Working Group of Obesity in China were applied to classify overweight and obesity based on measured weight and height. Multivariable logistic regression analyses were performed to examine the determinants of overweight/obesity and adoption of weight-loss practices. Results The prevalence of childhood overweight and obesity were 11.2 and 10.0 %, respectively. High birth weight (≥4.0 kg versus 2.5 ~ 4.0 kg, odd ratio [OR]: 2.34; 95 % confidence interval [CI]: 1.53-3.58), sugar-sweetened beverages (SSBs) intake (OR: 1.39; 95 % CI: 1.05-1.85), vegetable intake (OR: 1.12; 95 % CI: 1.01-1.24), and doing homework (OR: 1.24; 95 % CI: 1.08-1.43) were positively associated with obesity. Eating speed faster than peers was positively associated with obesity and yielded the highest OR (versus "as fast as peers", OR: 3.18; 95 % CI: 2.28-4.44). Approximately 57, 81 and 87 % of normal-weight, overweight and obese children, respectively, reported weight-loss practices. Self-perception of weight status presented as the strongest determinant for weight-loss practices. Conclusions The prevalence of overweight and obesity were high in Chinese children in Guangzhou, and both were higher than previous level in 2011. Further research should address the unhealthy dietary (e.g. SSBs intake, fast eating speed) and sedentary behaviors (e.g. doing homework) of these children. Moreover, an accurate perception of body weight can help promote the adoption of weight-loss practices in overweight and obese children.